ANALISIS DETEKSI KECURANGAN LAPORAN KEUANGAN DALAM DIMENSI FRAUD TRIANGLE - Julia Anggriani Irawan; Ida Ayu Nursanty; Rusdi Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze the detection of fraudulent financial statements in the dimensions of the fraud triangle. This type of research is associative research with an associative approach. The population in this study are manufacturing companies on the Indonesia Stock Exchange in 2019-2020, totaling 166 companies. The sample selection method used inthis research is the purposive sampling method. Samples that meet the riteria in this study were 95 companies. The data analysis used in this research is multipe regression analysis. The result of this study indicate that financial stability partially has a significant effect on financial statement fraud, financial targets partially has a significant effect on financial statement fraud. The nature of industry, ineffectove monitoring and audchange simultaneously have no significant effect on fraudulent financial.